Marine pollution: a study into the insufficiency of punishment imposed on oil spillage in Malaysia / Nadiia Md Yazid, Adam Idris and Syazwani Turiman - Md Yazid, Nadiia; Idris, Adam; Turiman, Syazwani (2007)
As a developing costal state, geographically located in a region of intense oil exploration and development activities and lying across the main oil transport route between the oil exporting countries in West Asia and Japan and other importing countries in the East, Malaysia cannot expect to totally escape pollution. The Straits of Malacca is by the same token one of the busiest waterways in the world. Traffics statistics show that the strait is passing by more that 60,000 vessel annually. Over three million barrels of petroleum products transverse the strait everyday of which'61% is carried by tankers of more than 100, 000 dwt and 30% by tankers more than 200, 000 dwt. In the course of their passage vessels are known to discharge their bilges and ballast waters with the upshot being that good part of which will end up on our beaches as oil residues of beach tar. In April 1979, a 10, 000 ton spill of crude oil due to a collision between two vessels in the South China Sea. Whereas in the Straits of Malacca, the "Showa Maru" spill in 1975 of 6,000 tons of crude oil. Collision and grounding remain the principal causes of oil spills in our water. There are several laws regulating oil spillage in Malaysia whereby punishment being imposed for the offences committed. Despite having these punishments which supposedly serves as deterrence for further offences, oil spillage still occur. Since it is so, it is the aims of this research to study into the sufficiency of the law whether there is it the cause for oil spillage to be continuously occurred.